PENGARUH MODEL KOOPERATIF TIPE STAD BERBANTUAN ALAT PERAGA PERMAINAN CONGKLAK MATERI KPK DAN FPB TERHADAP HASIL BELAJAR SISWA KELAS V - Inri Ani Gultom; Wildansyah Lubis; Elvi Mailani; Putra Afriadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effect of the Student Teams Achievement Division (STAD) cooperative learning model, supported by the congklak game as a teaching aid, on the mathematics learning outcomes of fifth-grade students at SDN 101776 Sampali regarding the topics of Least Common Multiple (LCM) and Greatest Common Factor (GCF). The study employed a quantitative approach using a quasi-experimental method and a pretest-posttest control group design. The research sample consisted of two classes: Class 5A, the experimental class, which received instruction using the STAD model supplemented with the congklak game; and Class V-B served as the control group, receiving instruction via the method frequently employed by the teacher (Problem-Based Learning).. The research instrument was a multiple-choice test that had passed validity, reliability, difficulty level, and discriminative power tests. Data were collected through observation, interviews, documentation, and pretest and posttest assessments, then analyzed using normality tests, homogeneity tests, and an Independent Samples t-test with the aid of IBM SPSS Statistics 26. The results showed that the average posttest score for the experimental class was 78.25, while that for the control class was 56.50. The improvement in learning outcomes in the experimental class was 70.5%, which was higher than that of the control class at 36.8%.The results of the hypothesis test show a t-value of 6.404 with degrees of freedom (df) = 38 and a significance level (Sig., 2-tailed) of 0.000. Since 0.000 < 0.05, H₀ is rejected and H₁ is accepted. Thus, the STAD cooperative learning model, supported by the congklak game as a teaching aid, has a positive and significant effect on students’ mathematics learning outcomes in the topics of LCM and GCF. This model has been proven to be more effective than PBL in improving the mathematics learning outcomes of elementary school students.